Teacher's beliefs on classroom management styles : a case study of a montessori kindergarten / Nur Haziratul Qudsiah Nor Hidan - Nor Hidan, Nur Haziratul Qudsiah (2014)
Instructional Leadership encompasses a number of aspects in the teaching and learning process including classroom management. As an effective classroom manager the teacher needs to take into consideration the many multi-faceted constructs of classroom management including behavioural management and instructional management. With scant empirical research on classroom management in the Malaysian preschool context,this descriptive case study aimed to explore teachers' beliefs toward classroom management styles in a Montessori kindergarten located in the Klang Valley. Besides that, this study also investigated the challenges that teachers faced and recommended strategies for effective classroom management. This study employed a mixed-methods approach involving both quantitative and qualitative data collection instruments such as a questionnaire and semi-structured interviews. Since this was a case study, the total population was involved in the study. A total of 71 respondents responded to the questionnaire whilst another eight respondents were randomly selected from the total population for the interview sessions. Findings revealed that a majority of the teachers used the interactionalist style in classroom management. The same style was also used by the teachers in the instructional management dimension while behavioural management dimension indicated that a majority of the teachers were interventionists. T-test analysis found that there is no significant difference in classroom management style with regards to teacher's age and training attendance. However, there was a significant difference between experienced and novice teachers with regards to instructional management.Interviews further revealed that teachers face challenges such as handling mixed age group, time management, language barrier, and children behaviour. Teachers also suggested aspects such as classroom setting, behavioural management, instructional management and training to improve classroom management. In conclusion, the findings that teachers are able to apply the Montessori approach in instructional management but could do with more training in understanding the concept of Montessori in behavioural management. Therefore, it is recommended for the school management to provide sufficient training to the teachers.